Current understanding of the impact of climate change on mental health within UK parliament - Pirkle, Lucy T.; Jennings, Neil; Vercammen, Ans; Lawrance, Emma L. (Frontiers in Public Health, 2022)
There is growing evidence that climate change is linked to adverse mental health outcomes, with both direct and indirect impacts already being felt globally, including within the United Kingdom (UK). With the UK parliament tasked with passing legislation to mitigate against and adapt to climate change, it is well placed to take a lead in implementing policies that reduce the impact of climate change on mental health and even provide mental health benefits (e.g., by increasing access to green space). The extent to which the UK parliament considers the relationship between climate change and mental health in its decision-making was previously unknown. We report, through quantitative thematic analysis of the UK Hansard database, that the UK parliament has only infrequently made links between climate change and mental health. Where links have been made, the primary focus of the speeches were around flooding and anxiety. Key mental health impacts of climate change reported in the academic literature, such as high temperature and suicides, or experiences of eco-anxiety, were found to be missing entirely. Further, policies suggested in UK parliament to minimise the impact of climate change on mental health were focused on pushing adaptation measures such as flood defences rather than climate mitigation, indicating potential missed opportunities for effective policies with co-benefits for tackling climate change and mental health simultaneously. Therefore, this research suggests a need to raise awareness for UK policymakers of the costs of climate inaction on mental health, and potential co-benefits of climate action on mental health. Our results provide insight into where links have and have not been made to date, to inform targeted awareness raising and ultimately equip policymakers to protect the UK from the increasingly large impacts of climate change on mental health.